The language of pop culture / edited by Valentin Werner - Werner, Valentin (Routledge studies in linguistics., 2018)
This collection brings together contributions from both leading and emerging scholars in one comprehensive volume to showcase the richness of linguistic approaches to the study of pop culture and their potential to inform linguistic theory building and analytical frameworks. The book features examples from a dynamic range of pop culture registers, including lyrics, the language of fictional TV series, comics, and musical subcultures, as a means of both providing a rigorous and robust description of these forms through the lens of linguistic study but also in outlining methodological issues involved in applying linguistic approaches. The volume also explores the didactic potential of pop culture, looking at the implementation of pop culture traditions in language learning settings. This collection offers unique insights into the interface of linguistic study and the broader paradigm of pop culture scholarship, making this an ideal resource for graduate students and researchers in applied linguistics, English language, media studies, cultural studies, and discourse analysis.